Characterization and Metabolism Effect of Seed Endophytic Bacteria Associated With Peanut Grown in South China - Li, Limei; Zhang, Zhi; Pan, Shiyu; Li, Ling; Li, Xiaoyun (Frontiers in Microbiology, 2019)
Endophytes are consider as excellent candidates for biocontrol agent and biofertilizer that are associated with plant growth promoting and health. Especially, seed-endophytic bacterium, alongside their role in plant growth and defense, they also provide benefit to the host plant’s offspring via vertical transmission. However, seed associated endophytic bacterium have not been fully explored and very little is known about that how they interact with peanut. Here, ten genus endophytic bacterium were isolated in peanut root tip from aseptic seedling or the soil seedling, respectively. Forty-two colonies were found in the soil seedling, and most of them belong to the Bacillus. While 8 colonies were detected in the aseptic seedling root tip, including Bacillus, Paenibacillus and Pantoea dispersa. Four Bacillus peanut GL1-GL4 (B.p.GL1-GL4) can produce bio-film. Both B.p.GL2 and Paenibacillus glycanilytics YMR3 (P.g.YMR3) possessed strongly amylolyticcapability and increased peanut biomass, while pantoea dispersa YMR1 (P.d.YMR1) caused peanut wilt. The P.g.YMR3 distributed mainly around or inside the vacuoles and transmitted from peanut to next generation along with the gynophores and ovules. The hexanoate, succinate and jasmonic acid were accumulated in peanut root tip after P.g.YMR3 incubated, while the linolenate decreased dramatically. It indicated that the P.g.YMR3 increased the JA (14.93 fold change) and modulated the metabolic of peanut to facilitate the nodules formation and growth promotion. These findings provide new understanding into plant-seed endophytic bacteria interactions in peanut.